2022
DOI: 10.1002/advs.202105059
|View full text |Cite
|
Sign up to set email alerts
|

Arrested in Glass: Actin within Sophisticated Architectures of Biosilica in Sponges

Abstract: Actin is a fundamental member of an ancient superfamily of structural intracellular proteins and plays a crucial role in cytoskeleton dynamics, ciliogenesis, phagocytosis, and force generation in both prokaryotes and eukaryotes. It is shown that actin has another function in metazoans: patterning biosilica deposition, a role that has spanned over 500 million years. Species of glass sponges (Hexactinellida) and demosponges (Demospongiae), representatives of the first metazoans, with a broad diversity of skeleta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 60 publications
0
26
0
Order By: Relevance
“…As it is shown in the present paper, the basic building blocks were spicules consisting of a central proteinaceous axial filament surrounded by alternating concentric interlayers of silica and organic matter. Ehrlich et al (2022) showed that axial filaments inside the spicules are found unbound to the mineralized phase. There are actin-rich axial filaments in microscleres.…”
Section: Discussionmentioning
confidence: 99%
“…As it is shown in the present paper, the basic building blocks were spicules consisting of a central proteinaceous axial filament surrounded by alternating concentric interlayers of silica and organic matter. Ehrlich et al (2022) showed that axial filaments inside the spicules are found unbound to the mineralized phase. There are actin-rich axial filaments in microscleres.…”
Section: Discussionmentioning
confidence: 99%
“…In some groups, they are arranged into rigid (fused) skeletal structures. Siliceous spicules are biocomposites that incorporate organic material in their structure—a special protein complex forming an axial filament situated in the interior of most siliceous spicules (Ehrlich et al, 2022; Görlich et al, 2020; Uriz, 2006; Uriz et al, 2003). Collagen or chitin matrix may be also present inside the silica spicules (Ehrlich et al, 2007, 2017, 2018; Fromont et al, 2019; Pisera et al, 2021).…”
Section: Poriferan Tissue and Skeletonmentioning
confidence: 99%
“…Before we can reach a mechanistic understanding of the dissolution of biogenic silica, further characterization of the BSi behavior in seawater and Si-desaturated solutions rich in ions is required. Likewise, a recent surprising report of actin deeply embedded in the silica of demosponges and hexactinellids (Ehrlich et al, 2022) emphasizes the need of deepening into the atom-level characterization of the complexation of BSi with organic elements, which may significantly determine dissolution patterns. The persisting lack of knowledge in this sense is relevant because the dissolution kinetics of the biogenic silica reservoirs in the water column and the sediments are one of the main controls of the biogeochemical cycling of silicon in the ocean.…”
Section: Dissolution Patterns and Their Causesmentioning
confidence: 99%